Основные ожидаемые проблемы в период осуществления реформы "Индустрия – 4.0" и пути их практического решения на основе повышения эффективности используемых мехатронных систем - Турманидзе, Р. С.; Бачанадзе, В. И.; Попхадзе, Г. З. (НТУ "ХПИ", 2018)
This work presents the results of an analysis of the main expected potential problems that may occur in the implementation of the INDUSTRY - 4.0 reform. It is proved that the pace and level of development of this reform will largely be determined by the effectiveness of the used mechatronic systems. It has also been established that as a result of systematic miniaturization of the nodes of radio-electronic equipment and microelectronic equipment and microelectronic technology, the main problem of these reforms and the implementation of complex technological processes is instrumental support, especially cutting micro-tools. Therefore, the examples of these micro-tools show methods for improving their performance characteristics.
Keywords: осевое усилие; крутящий момент; сверло; шлифовальный круг; зубчато-реечная пара; электротехническая промышленность